An innovative technique to treat epulis fissuratum: A case report - Chaima Khalifa (SAGE Publishing, 2021)
The purpose of this article is to present a case demonstrating the treatment of epulis fissuratum due to a poorly adapted prosthesis using a single surgical procedure involving conventional excision and free gingival graft. We, herein, present a case involving a 58-year-old patient with epulis fissuratum. Treatment of this case was essential due to the masticatory problems. This technique can be effective to deepen the height of the residual alveolar ridge and to increase the amount of keratinized tissue.